Effects of sodium 18 beta-glycrrhetinic acid on the production of active oxygen species and the concentration of intracellular free Ca2+ in rat neutrophils - Wu Yong-jie; Li Xin-fang (Acta Pharmacologica Sinica, 2016)
The effects of sodium 18 beta-glycyrrhetinic acid (SGA) on the production of active oxygen species (AOS) and the concentration of intracellular free Ca2+ ([Ca2+]i) in the rat neutrophils were studied by the methods of luminoldependent chemiluminescence and calcium indicator Fura-2 loading. The results showed that SGA 0.8-12.7 mumol.L-1 selectively inhibited calcium inophore A-23187-stimulated AOS production with IC50 1.4 mumol.L-1, while SGA 25.4-203 mumol.L-1 stimulated neutrophils to generate AOS and potentiated the action of chemotactic peptide f-MLP on inducing AOS production. SGA 25.4-203 or 6.3-50.7 mumol.L-1 depressed the [Ca2+]i rise in neutrophils stimulated by A-23187 or f-MLP; in the contrast, verapamil or diltiazem has higher effective concentration more than 100 or 200 mumol.L-1 to f-MLP and left [Ca2+]i rise induced by A-23187 unaffected. SGA 101.5-203 mumol.L-1 also caused [Ca2+]i rise in neutrophils. The result analysis indicate that the effect of SGA on AOS production has no relationship with its regulation to [Ca2+]i in neutrophils.